2014
DOI: 10.1186/1756-8935-7-17
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation reader MECP2: cell type- and differentiation stage-specific protein distribution

Abstract: BackgroundMethyl-CpG binding protein 2 (MECP2) is a protein that specifically binds methylated DNA, thus regulating transcription and chromatin organization. Mutations in the gene have been identified as the principal cause of Rett syndrome, a severe neurological disorder. Although the role of MECP2 has been extensively studied in nervous tissues, still very little is known about its function and cell type specific distribution in other tissues.ResultsUsing immunostaining on tissue cryosections, we characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 69 publications
10
38
0
Order By: Relevance
“…Our general observation is that MeCP2 expression scales with nuclear size, and cerebellar granule cells express the lowest amount of MeCP2 of the cell types examined in this study (data not shown). The lack of changes in H4K20me3 distribution in cerebellar granule cells agrees with results from a previous study that did not find differences in histone modifications in Mecp2 -null retinal neurons (Song et al, 2014). These results stress the importance of cell sorting or in situ approaches when studying gene expression in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…Our general observation is that MeCP2 expression scales with nuclear size, and cerebellar granule cells express the lowest amount of MeCP2 of the cell types examined in this study (data not shown). The lack of changes in H4K20me3 distribution in cerebellar granule cells agrees with results from a previous study that did not find differences in histone modifications in Mecp2 -null retinal neurons (Song et al, 2014). These results stress the importance of cell sorting or in situ approaches when studying gene expression in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, MeCP2 was observed in a few astrocytes (Fig. 6A, B), consistent with previous findings [11,28]. Interestingly, pS80 MeCP2, pS421 MeCP2, and pS292 MeCP2 were also detected in astrocytes, although doublelabeled cells were extremely few (Fig.…”
Section: Cell Types Expressing Mecp2 and The Pmecp2s In The Postnatalsupporting
confidence: 91%
“…50,51 Deletion of Mecp2 from glia in mice has relatively minor phenotypic consequences but a restoration of MeCP2 to astrocytes in an otherwise MeCP2-deficient nervous system results in a partial amelioration of phenotypes including a normalisation of breathing patterns, motor activities and anxiety. 48 As also indicated in primary culture experiments, 52 MeCP2 in glial cells may contributing to certain non-cell autonomous functions such as supporting normal dendritic morphology through the release of trophic factors within the nervous system.…”
Section: Mecp2 Is Essential For Normal Brain Functionmentioning
confidence: 99%